2009
DOI: 10.1007/s10499-009-9287-x
|View full text |Cite
|
Sign up to set email alerts
|

Oral and parenteral vaccines against Flavobacterium columnare: evaluation of humoral immune response by ELISA and in vivo efficiency in Nile tilapia (Oreochromis niloticus)

Abstract: Flavobacterium columnare is a bacterial pathogen for many freshwater fish species. It is responsible for outbreaks in fish farms worldwide, causing high mortality rates. Fish vaccination is a potential approach for prevention and control of disease, with oral vaccines suitable for fish because of their easier application, low cost and minimum stress to fish. Alginate microparticles have been widely used as controlled release systems, including for fish vaccination. The aim of this study was to evaluate the cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…With this in mind, it would seem prudent to optimize formalin concentration and exposure time and to keep it to a minimum in future studies. However, formalin‐killed vaccine preparations have been quite extensively evaluated in fish and are often successful (Azad et al ., ; Ji et al ., ; Kubilay et al ., ; Leal et al ., ; Locke et al ., ). Commonly, these are formalin‐killed bacterins of fish pathogens rather than bacterins made from heterologous expression hosts.…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, it would seem prudent to optimize formalin concentration and exposure time and to keep it to a minimum in future studies. However, formalin‐killed vaccine preparations have been quite extensively evaluated in fish and are often successful (Azad et al ., ; Ji et al ., ; Kubilay et al ., ; Leal et al ., ; Locke et al ., ). Commonly, these are formalin‐killed bacterins of fish pathogens rather than bacterins made from heterologous expression hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EP is used as a helper substance (adjuvant) in veterinary rabies vaccines to activate antigen presenting cells and to stimulate these cells to produce more cytokines which activate lymphocytes producing specific antibodies (Liu et al 2012). Previous studies have evaluated the efficiency of different vaccine preparations against F. columnare infection and the humoral immune response induced by them (Grabowski et al 2004, Shoemaker et al 2007, Leal et al 2010. Grabowski et al (2004) reported that formalin-killed F. columnare administered intraperitoneally and by immersion could not stimulate a specific immune response in Nile tilapia without Freund;s complete adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the oral administration of microparticles of Flavobacterium to Nile tilapia (Oreochromis niloticus) did not stimulate the production of antibodies in serum, but intraperitoneal and intramuscular administration did. This stimulation does not correlate with protection against infection with any of the studied vaccines (Leal et al, 2010). However, better results were obtained when bacterin microparticles were used as an oral booster after intraperitoneal vaccination with naked bacterin, reaching 87% relative survival (RPS) Romalde et al, 2004).…”
Section: Bacterial Antigens Encapsulated In Alginatementioning
confidence: 98%
“…One of the characteristics of alginate microparticles that makes them useful for delivering drugs is their resistance to acid pH, which impedes the release of the antigen in the stomach of the fi sh (pH 2-4) and favors their its release in the foregut or hindgut (pH 7 and 8.3, respectively) (Joosten et al, 1997;Leal et al, 2010;Rodrigues et al, 2006;Salinas et al, 2011). Microparticles from 10 to 50 μm can be effi cient for vaccinating, although it has been shown that the smaller the size, the greater the effi ciency of incorporation (Rodrigues et al, 2006;Romalde et al, 2004).…”
Section: Alginatementioning
confidence: 99%